Induction of host resistance to Rhipicephalus appendiculatus in rabbits: Effects of immunizing with detergent-solubilized tick tissue proteins - Dhadialla, T. S.; Rutti, Bernard; Brossard, Michel (My University, 1990)
Resistance to the hard tick, Rhipicephalus appendiculatus, was induced in rabbits by immunizing them with tick tissue proteins extracted with a detergent, Triton X-100. There was 25% mortality in female ticks fed on immunized rabbits as compared with those fed on controls. Similarly, there was a 40% and 60% reduction in the engorged weight and the weight of egg batches, respectively, of ticks fed on immunized rabbits. Western blot analysis of detergent-solubilized tick tissue Western blot analysis of detergent-solubilized tick tissue proteins, carried out using immune sera, recognized a complex pattern of proteins. A strong reaction was observed with proteins with apparent molecular weights of 94000 and 40000 daltons.